HUBUNGAN KARAKTERISTIK RESPONDEN DAN FAKTOR LINGKUNGAN FISIK RUMAH TERHADAP KEJADIAN MALARIA DI DESA KAMPUNG PADANG KEC. PANYABUNGAN KAB. MADINA TAHUN 2014 - rofiqoh hasibuan; indra chahaya; wirsal hasan (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRAC Kampung Padang village is one of the villages in the Panyabungan district are endemic Malaria with AMI (Annual Malaria Incidence) of 29.21 ‰ and API (Annual Parasite Incidence) of 63.41 ‰. Incidence of malaria caused by human contact with malaria mosquitoes and supported by the housing and unfavorable environmental conditions. The purpose of this study to know the relationship of the characteristics of respondents and the physical environmental factors on the incidence of malaria in the Kampung Padang village Panyabungan of District Mandailing Natal of Subdistrict. This research was conducted with non parametric methods of analysis with Case Control design. The total sample of 85 heads of families consisting of 35 cases and 50 controls. Data were analyzed with non-parametric analysis methods of analysis with Chi Square test. The results obtained that there is a relationship of the education  (p = 0,009, OR = 0,304: 95% CI = 0,124-0,750), employment (p = 0,001),, social cultural, wire gauze on ventilation (p = 0.001), lagit-sky home (p = 0,001, OR = 0,135: 95% CI = 0,051-0,358), wall density (p = 0,001, OR = 0,160: 95% CI = 0,059-0,439), humidity (p = 0,001, OR = 5,608: 95% CI = 2,152-14,611) and lighting (p = 0,007, OR = 3,656: 95% CI = 1,394-9,592)on the incidence of malaria. It is suggested to health department to educate the community particulary Malaria disease. This can be done through socialization with PKK, IHC, or community health center and should increase the activity PJB (Larva Monitoring Periodic) in each home or in public places such as schools, mosques, markets, terminals, and raised his interpreter monitors larvae and for the people should pay attention to the cleanliness of the environment. Key Words: Characteristics, Physical Appearance, Environmental, Malaria